Fluid Therapy in Pulmonary Disease: How Careful Do We Need to Be? - Adamantos, Sophie (Frontiers in Veterinary Science, 2021)
Intravenous fluid therapy is a vital and life-saving therapeutic in veterinary medicine. In the absence of heart or lung disease, trauma or sepsis there is limited evidence that fluid therapy will have a detrimental effect on lung function. In healthy dogs there is a reasonable level of experimental evidence that supraphysiologic rates of fluid are required before signs of fluid overload are made evident. In cats, however, this may not be the case. There are higher rates of asymptomatic myocardial disease, but even in the absence of that it seems that some cats may be susceptible to fluid overload. Where systemic inflammation already exists the careful homeostatic and protective strategies within the lung are deranged, and increases in hydrostatic pressure are more likely to result in fluid movement into the lung tissues resulting in fluid overload. Strategies including restricting the use of intravenous crystalloid fluid administration and using blood products for management of severe haemorrhage are of increasing importance in human trauma and seem to be associated with fewer pulmonary complications, and lower mortality. Managing dogs and cats with sepsis and ARDS is already challenging, but ensuring adequate vascular expansion needs to be balanced with avoiding excessing administration which may impact on pulmonary function. While fluids remain crucial to management of these conditions, there will be an ongoing requirement to balance need without providing excess. The use of point of care ultrasound may provide us with a non-invasive and accessible way to do this.